Behavioral modeling of the NB-IoT downlink physical layer - Rosa, José Manuel Nunes de Brito (2020)
The Internet of Things (IoT) paradigm de nes a fully connected network of devices enabling new forms of interaction between users and devices. The constant growth of these networks, as well as an increasing demand for more reliable, low bit rate and massive communication data ows lead to the emergence of new technologies and set of standards, such as, the Low Power Wide Area Networks (LPWAN). In June 2016, 3GPP, the consortium responsible for LTE development and standardization, released a new licensed band based standard, named Narrow Band (NB) IoT. NB-IoT was designed based on the same principles of other LPWAN standards, providing better coverage and additionally an easier integration on existing cellular systems. In this dissertation a study on the NB-IoT Physical Layer is presented along with an open source behavioral implementation in MATLAB of the downlink transmission and reception chains. The system generates and recovers one radio frame successfully performings procedures such as MIB and SIB1-N extracting along with scheduling and recovering data scheduled through control channels by higher layer paramenters. The project models and executes the downlink transmission (eNodeB) and reception (terminal) PHYs either in a pure simulation environment using di erent channel models, as well as integrated with an USRP software de ned radio device for co-simulation. The simulation and co-simulation results are presented evaluating the transmission's quality and performance of the implemented Zero Forcing equalizer.